PERAN BRAND AWARENESS MEMEDIASI SOCIAL MEDIA MARKETING TERHADAP NIAT BELI SEPATU NIKE DI KOTA DENPASAR - Dindasari, Made Ayuni; Sukawati, Tjok Gde Raka (E-Jurnal Manajemen; Vol 11 No 10 (2022)DO - 10.24843/EJMUNUD.2022.v11.i10.p03, 2022)
Purchase intention is an activity or a person's behavior that arises through his response to show the customer's desire to purchase an object. The purpose of this study was to determine the role of brand awareness in mediating social media marketing on the intention to buy Nike shoes in Denpasar City. This research was conducted in Denpasar City. The number of samples taken as many as 130 respondents who are respondents who have never bought Nike shoes. Data was collected through interviews, observations, and questionnaires. The analysis technique used is path analysis and the Sobel test. The better a brand is in social media marketing, will increase brand awareness among consumers of the product so consumers' purchase intentions will also increase. Keywords : social media marketing; brand awareness; purchase intention